Systemic inflammation after cardiac surgery - Duggan, Edel (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2008)
Genetically determined inter-individual variation in cytokine production, influences outcome in patients with systemic inflammation and severe sepsis. However outcome in patients with sepsis is also dependant on the presence of co existing disease and the interaction between infection and inflammation. Due to this heterogeneity, the role of genetic factors in the generation of systemic inflammation is difficult to study in septic patients. Our study overcomes this by examining systemic inflammation that occurs postoperatively in cardiac surgical patients in a sterile setting. Using real time polymerase chain reaction (PCR), we measured interleukin 10 (IL 10) and tumour necrosis factor alpha (TNF a) messenger RNA in peripheral mononuclear cells at timed points after cardiopulmonary bypass. A low IL 10:TNF a mRNA ratio manifested systemically as haemodynamic instability within 24hrs post cardiac bypass. We also determined cytokine related single nucleotide polymorphisms using restriction fragment length polymorphism, and taqman technology. Haplotype analysis was perfomed using Phase II software for both TNF and IL 10 polymorphisms.
Keywords: Surgery, M.D.; M.D. Trinity College Dublin